Child's legal personality: actualization of opportunities and their limitations - N. N. Tarusina; E. V. Koneva; S. V. Simonova (Правоприменение, 2023)
The subject of this research is the concept of a child’s legal capacity in an interdisciplinary context and the validity of various approaches for determining the essence and scope of a child’s legal capacity in terms of Russian public and private legislation and to provide suggestions for improvement.Methodology: The authors’ general research methods for cognition are: analysis, synthesis, and abstraction. This research is also based on legal acts and judicial practice, as well as on the opinions of scientists.Results: On the one hand, differentiations in terms of the essence, structure and scope of a child’s legal capacity within the branches of Russian law are justified according to the specifics of their subject and methods of legal regulation. On the other hand, the differences in approaches presented in them, especially according to age criterion, are far from universally justified, and this is especially characteristic of the active component of legal personality – or legal capacity. Thus, 14 and 16 are the ages of legal capacity in terms of constitutional law; 6, 14 and 16 for civil law; 14, 15 and 16 for labour law; 15 for medical law; 10, 14, 15, 16 for family law; etc. The law on education does not indicate any age benchmarks, being oriented towards the school education periods. At the same time, the lower boundaries of ‘minimal legal capacity’ are established only for the sake of civil legal relations and administrative and criminal liability. In other cases, in the assessment of a child’s ability to make legally significant decisions, the law enforcement officer considers a child’s individual psychological characteristics. Typically this approach proves to be correct. Psychological data indicate the development of an acceptable level of cognitive ability by the age of 12; therefore, the formally enshrined concept of child consent to certain legally significant acts beginning at the age of 10 requires discussion and possible adjustment. The ages of 14 and 16 as starting points for basic elements of the legal capacity (legal personality) are reasonable and must be applied systematically; other intermediate solutions are not justified. In terms of a generally correct decision with regard to the moment when the age of legal capacity begins, it would be reasonable to correlate this with the protection of a child’s interests before his/her birth. There is no unified approach to understanding a child’s ability to perform legal duties: in civil law such ability is denied, while in other legal spheres it exists. As for family law, it should be assimilated into the general group. Conclusions: the concept of a child’s legal capacity requires systematization and enhancement as a prerequisite for a reasonable and justified arrangement of children's world – both within the family and in the public sphere.